Online safety in Kenya: A snapshot of the Silicon Savannah - Ndanu Mutua, Sylvia; Zhang , Kai (Multidisciplinary Journal of Technical University of Mombasa, 2023)
This article provides an overview of online safety in Kenya by outlining key threats and the interventions that have been implemented to combat these threats. Using the social responsibility theory, this article further explores internet users’ perceptions of online social responsibility in cyberspace. Results of the study indicate that the internet media environment which is characterized by interactivity significantly moderates the internet users’ perception of their online social responsibility. However, despite the court suspensions of some of the laws, the existing online content regulations still have a significant influence on online safety. Consequently, the article advocates the need to associate the concept of human dignity with the responsibilities that each person must take for his or her online actions. This implies that one’s online dignity would entail one owning up to their online conduct in the quest for safe, respectful, inclusive, and harmonious cyberspace. Also, greater online social responsibility by Kenyan internet users would be necessary to foster free speech, open access, and a social culture of respecting others, and not harming others in cyberspace.